Board Turnover and Reorganisation Outcomes: Evidence from Voluntary Administration. Issue 3 (21st October 2018) - Chapple, Larelle; Routledge, James
Abstract: This paper examines the relation between board turnover and the likelihood that a company that enters voluntary administration will conclude a deed of company arrangement with its creditors, which provides stakeholders with a better outcome than would be achieved by liquidation. We examine director turnover generally, as well as turnover of specific board personnel including the CEO or managing director and the board chairperson. A significant positive relation is found between a deed outcome and the percentage of director turnover and turnover of a CEO or managing director. We interact board turnover variables and company size and find that the turnover benefit is reduced as company size increases and the complexity of the administration becomes greater. The results inform a controversial and largely unanswered question as to whether board turnover leads to better outcomes for insolvent companies. Moreover, the results have implications for the Australian voluntary administration legislation because they suggest that there are difficulties applying it to large and complex corporate insolvencies. Abstract : This paper examines the relation between board turnover and the likelihood that a company entering voluntary administration will conclude a deed agreement with creditors. Director or chief executive or managing director turnover increases the likelihood, but not when the administration is complex.